2014
DOI: 10.1039/c3nr05340g
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing surface-extruded plastic flow of SiOxamorphous nanowire as athermally induced by electron beam irradiation

Abstract: Nanoinstability and nanoprocessing of a SiOx amorphous nanowire at room temperature as induced by in situ electron beam irradiation in transmission electron microscopy are systematically investigated. It is demonstrated that in contrast to the crystalline nanowires where only the beam-induced ablation of atoms was observed, the amorphous nanowire herein can give rise to an arresting beam-induced surface-extruded plastic flow of massive atoms and surface migration of atoms in addition to the beam-induced ablati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 24 publications
3
53
0
Order By: Relevance
“…The additional energy from the e-beam is able to reconfigure the structure and the bonding condition in onedimensional nanomaterials. The e-beam effect has been proved as a valid method to achieve local modifications of nanomaterials by our work and some other reports [31][32][33]. We have also demonstrated that in situ TEM and aberrationcorrected HRTEM are very powerful techniques for studying these local microscopic structural transformations.…”
Section: Discussionmentioning
confidence: 64%
“…The additional energy from the e-beam is able to reconfigure the structure and the bonding condition in onedimensional nanomaterials. The e-beam effect has been proved as a valid method to achieve local modifications of nanomaterials by our work and some other reports [31][32][33]. We have also demonstrated that in situ TEM and aberrationcorrected HRTEM are very powerful techniques for studying these local microscopic structural transformations.…”
Section: Discussionmentioning
confidence: 64%
“…It is worth noting that our mechanical tests were carried out inside a SEM. It has been reported that electron beam irradiation could induce softening in the ionic-and covalently-bonded samples [11,20,21]. If this effect is also present for iron-rich and fly ash particles, their H c without e-beam effect could be even higher.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, even more universally, along with other experiments 14,15,22,23 (also X. F. Zhu et al, manuscripts in preparation or to be submitted), the experiment herein further confirms that the general principle of nanosize effect (i.e., nanocurature effect as specified in this letter and also including low dimensionconfinement effect at nanoscale) and nanotime effect (i.e., energetic beam-induced athermal activation effect or energetic beam induced-atomic vibration instability and soft mode effect as specified in this letter) as predicted in earlier publications [16][17][18] can be extended for elucidation of nanoinstability of LDNs of different types under such irradiations as well as for elucidation of irradiation of other energetic beams such as ion or photon (i.e., laser) beam. …”
Section: -3mentioning
confidence: 99%